Saccharomyces cerevisiae growth kinetics study dairy byproduct - Sulyok, Erika; Bró, Györgyi; Tamás, János (Acta Agraria Debreceniensis, 2013)
By guess, annual volume of milk whey is 185–190 million tons and this volume probably will increase next years. Whey has significant biochemical oxygen demand due to its high organic matter content so whey as sewage is one of the most pollutant by-products in the food industry. Apart from environmental pollution, benefit of several whey constituents for human health is another reason to utilize whey. Corn and potato, as well as the processing of milk in the food industry in large quantities of by-products generated by low cost, substantial quantities of starch and lactic acid, which are due to high biological oxygen demand are considered as hazardous waste. Some of them are destroyed sewage storage tanks, and those products are excellent substrates for the growth of microorganisms could be. The traditional nutrient solution optimization methods are solution and time-consuming and are not able to determine the real optimum because of the interaction of factors involved.